Interdependencies of cellular and humoral immune responses in heterologous and homologous SARS‐CoV‐2 vaccination. Issue 8 (16th February 2022) - Hollstein, Moritz M.; Münsterkötter, Lennart; Schön, Michael P.; Bergmann, Armin; Husar, Thea M.; Abratis, Anna; Eidizadeh, Abass; Schaffrinski, Meike; Zachmann, Karolin; Schmitz, Anne; Holsapple, Jason S.; Stanisz‐Bogeski, Hedwig; et al.
Abstract: Background: Homologous and heterologous SARS‐CoV‐2 vaccinations yield different spike protein‐directed humoral and cellular immune responses. This study aimed to explore their currently unknown interdependencies. Methods: COV‐ADAPT is a prospective, observational cohort study of 417 healthcare workers who received vaccination with homologous ChAdOx1 nCoV‐19, homologous BNT162b2 or with heterologous ChAdOx1 nCoV‐19/BNT162b2. We assessed humoral (anti‐spike‐RBD‐IgG, neutralizing antibodies, and avidity) and cellular (spike‐induced T‐cell interferon‐γ release) immune responses in blood samples up to 2 weeks before (T1) and 2–12 weeks following secondary immunization (T2). Results: Initial vaccination with ChAdOx1 nCoV‐19 resulted in lower anti‐spike‐RBD‐IgG compared with BNT162b2 (70 ± 114 vs. 226 ± 279 BAU/ml, p < .01) at T1. Booster vaccination with BNT162b2 proved superior to ChAdOx1 nCoV‐19 at T2 (anti‐spike‐RBD‐IgG: ChAdOx1 nCoV‐19/BNT162b2 2387 ± 1627 and homologous BNT162b2 3202 ± 2184 vs. homologous ChAdOx1 nCoV‐19 413 ± 461 BAU/ml, both p < .001; spike‐induced T‐cell interferon‐γ release: ChAdOx1 nCoV‐19/BNT162b2 5069 ± 6733 and homologous BNT162b2 4880 ± 7570 vs. homologous ChAdOx1 nCoV‐19 1152 ± 2243 mIU/ml, both p < .001). No significant differences were detected between BNT162b2‐boostered groups at T2. For ChAdOx1 nCoV‐19, no booster effect on T‐cell activation could be observed. We found associations between anti‐spike‐RBD‐IgG levels (ChAdOx1 nCoV‐19/BNT162b2 and homologous BNT162b2) and T‐cell responses (homologous ChAdOx1 nCoV‐19 and ChAdOx1 nCoV‐19/BNT162b2) from T1 to T2. Additionally, anti‐spike‐RBD‐IgG and T‐cell response were linked at both time points (all groups combined). All regimes yielded neutralizing antibodies and increased antibody avidity at T2. Conclusions: Interdependencies between humoral and cellular immune responses differ between common SARS‐CoV‐2 vaccination regimes. T‐cell activation is unlikely to compensate for poor humoral responses. Abstract : Booster with BNT162b2 elicits strong humoral and cellular immune responses independent of the prime vaccination, whereas ChAdOx1 nCoV‐19 booster does not further enhance the cellular response. Levels of humoral and cellular immune responses following COVID‐19 vaccinations are related and interdependencies between them differ amongst vaccination regimes. Poor humoral immune responses are unlikely to be compensated by strong cellular activation.Abbreviations: COVID‐19, coronavirus disease 2019; IFN, interferon; RBD, receptor‐binding domain; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; T, time points